2018
DOI: 10.1099/jmm.0.000835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the microbial pattern of periprosthetic joint infections of the hip and knee

Abstract: Patients suffering PJI present a certain risk profile with many comorbidities, e.g. high age and obesity. The observed microbiological pattern demonstrates the rise of high-resistance pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 24 publications
1
56
0
10
Order By: Relevance
“…We also found that MDR nonfermenters and MDR S. aureus rates were higher at tropical sites vs. subtropical. Reported cases of MDR nonfermenters in the orthopaedic literature are too low to be comparable; however, we note that our rates of MDR S. aureus are consistent with other studies [20,21,[23][24][25][26]. In their assessment of pathogens cultured from surgical site infections following joint arthroplasty and spinal fusions, Norton et al found that 33% of S. aureus was methicillin-resistant and similarly, Dudareva et al identified that 22.5% of S. aureus species cultured from chronic osteomyelitis patients in the United Kingdom were MDR [20,24].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that MDR nonfermenters and MDR S. aureus rates were higher at tropical sites vs. subtropical. Reported cases of MDR nonfermenters in the orthopaedic literature are too low to be comparable; however, we note that our rates of MDR S. aureus are consistent with other studies [20,21,[23][24][25][26]. In their assessment of pathogens cultured from surgical site infections following joint arthroplasty and spinal fusions, Norton et al found that 33% of S. aureus was methicillin-resistant and similarly, Dudareva et al identified that 22.5% of S. aureus species cultured from chronic osteomyelitis patients in the United Kingdom were MDR [20,24].…”
Section: Discussionsupporting
confidence: 91%
“…Systemic antibiotic therapy is a critical aspect of treating PJI, however, increasing bacterial resistance to conventional antimicrobial agents creates significant treatment challenges 146,147 . Over the past decade, novel antibiotics with broad‐spectrum activity against Gram‐positive organisms such as daptomycin, which is a cyclic lipopeptide, and linezolid, an oxazolidinone, have been developed to expand treatment options for resistant infections 108–110 .…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%
“…Тенденцию к увеличению числа высокорезистентных возбудителей ППИ, таких как MRSE, бактерий-продуцентов бета-лактамаз расширенного спектра, ампициллин-резистентных энтерококков, Acinetobacter spp. и ванкомицин-устойчивых энтерококков отмечают также T. Rosteius с соавторами [3]. Очевидно, что уровень резистентности возбудителей значимо влияет на исход лечения вне зависимости от хирургической тактики.…”
Section: статистический анализunclassified
“…Все современные лечебные алгоритмы указанной патологии учитывают длительность и характер течения инфекционного процесса, состояние тканей, окружающих эндопротез, вид возбудителя, его антибиотикорезистентность, а также состояние пациента [1]. В последние годы особое внимание стали уделять полирезистентным возбудителям ППИ, снижающим эффективность санирующих операций и этиотропной антибактериальной терапии и нередко приводящим к многократному рецидивированию инфекционного процесса [2,3,4]. Это привело к закономерному появлению в научной литературе нового термина «difficult to treat», характеризующего трудноизлечимую перипротезную инфекцию (ТИ ППИ), обусловленную трудными для эрадикации (ТДЭ) возбудителями, устойчивыми к антибиотикам, активными в отношении микробных биопленок.…”
Section: Introductionunclassified